Impact of nighttime versus daytime emergency surgery on the outcome of necrotising enterocolitis - Mbonisweni, Akhona (Division of General Surgery, 2024)
Background Necrotising enterocolitis (NEC) is the most common neonatal gastrointestinal surgical emergency, with a high mortality. We hypothesised that nighttime (NT) surgery was associated with higher mortality, intra-operative adverse events (AE) and post operative complications. Objectives To determine differences in mortality, intra operative AE and post operative complications between NT and DT surgery for NEC. Methods Patients with NEC (n=96) who needed surgical intervention (2015 - 2019) were retrospectively reviewed at a free-standing tertiary paediatric hospital. Differences in mortality, intraoperative AE, post operative surgical complications and length of intensive care unit stay were assessed for NT versus daytime (DT) surgery. Results Thirty-three patients (34.4%) were operated during NT. Demographics of the two groups were similar for gestational age, birth weight, sex, and age at operation. NT patients required increased inotropic support pre-operatively (p=.013) and had shorter time from diagnosis to surgical intervention (p<.001). Other preoperative characteristics (SNAPPE II score, haemoglobin, platelet count, C-reactive protein, and serum sodium) showed no statistically significant differences. Duration of anaesthesia and operative time were shorter at NT (p=.01 and p=.002 respectively). Red blood cell transfusion rates were higher at NT (p=.03). “Damage control” surgery was more common at NT (p=.01) and associated with 25% 30-day mortality compared to 33% for other patients (p=.03). Other operative characteristics and intraoperative AE were similar. Thirty-day mortality and enterostomy complications were higher for NT surgery (p=.02 and p=.013), while overall mortality and incidence of other post-operative surgical complications were not significantly different between groups. Longer duration of surgery collerated with increased risk of mortality for both DT and NT surgery (p=.009 and p=.023 respectively). Conclusion Patients operated at night required more inotropes and red cell transfusion, and had an increased 30-day mortality and post-operative enterostomy complications. The incidence of intraoperative AE and other post operative complications were similar between groups. A damage control mindset was more prevalent at NT and may reduce mortality. The time of day for surgery for NEC depends on acuity of disease and local resources. NT surgery was found to be as safe as DT surgery in our institution. Further research on damage control surgery outcomes and reduction of stoma complications is needed.